Implementasi Pembelajaran Berdiferensiasi Pada Sekolah Penggerak SD Negeri Rejoagung 02 - Novia Setyoningtyas, Novia; Peni Retnowati; Ulin Nafi’ah; Ahmad Hariyadi; Sri Utamingsih (Pena Anda: Jurnal Pendidikan Sekolah Dasar, 2025)
Differentiated learning is an approach that accommodates various needs, learning styles, and abilities of students in the education process. This study aims to explore effective management strategies in the implementation of differentiated learning, from the preparation process, implementation and evaluation and its impact on improving the quality of education in schools. The Driving School has an obligation to implement education through differentiated learning, the problem encountered at the driving school of SD Negeri Rejoagung 02 is that it has not been optimal in preparing the implementation of differentiated learning. The research approach uses a descriptive qualitative approach, data collection techniques are carried out through observation, interviews, questionnaires, field notes, and documentation on the preparation, implementation and evaluation of the implementation of differentiated learning at SD Negeri Rejoagung 02. The results of the study indicate that the preparation for the implementation of differentiated learning at SD Negeri Rejoagung 02 through training activities (In House Training) for all educators has a positive impact on teachers at SD Negeri Rejoagung 02, providing knowledge and improving teacher competence in the implementation of differentiated learning. The implementation of differentiated learning at Rejoagung 02 Elementary School has been running well in accordance with the learning needs of students and has had an impact on improving the quality of learning at Rejoagung 02 Elementary School.